Cellular senescence in colorectal cancer: its occurrence, effect and therapy - Liang, Yabing; Wang, Miao; Wang, Xianjue; Yang, Zhiqing; Wang, Shucheng; Li, Fengyi; Su, Liya; Yang, Ling (Frontiers in Oncology, 2025)
Colorectal cancer (CRC) is one of the most common malignant tumors worldwide. Although the use of small molecule drugs or targeted drugs has shown significant efficacy in the treatment of CRC, the drug resistance after treatment and the high recurrence and metastasis rate are the key obstacles affecting the success rate of treatment and survival of patients. Cellular senescence constitutes an important barrier to tumor progression. Senescent tumor cells and stromal cells are among the reasons for cancer treatment resistance. Different senescent programs can exert inhibitory or promotional effects on CRC. In serrated adenomas of colon, the senescence induced by intrinsic oncogenes serves as a threshold that precancerous lesions must traverse to develop into cancer. And the exposing of anti-cancer treatment, such as chemotherapy and radiotherapy, some cells also enter a senescent state, presenting a stable cell cycle arrest and senescence-associated secretory phenotype (SASP). SASP can activate immune surveillance but also contribute to the maintenance of cellular senescence microenvironment to help the CRC progression. Hence, in the pursuit of effective CRC treatment strategies, the issue of senescent cells is inevitable. By targeting features of senescent cells, such as upregulated anti-apoptotic signaling, altered metabolic signaling, and differential SASP secretion, depletion of senescent cells could be a promising strategy for the treatment of CRC. This review summarizes the endogenous and exogenous factors leading to cell senescence in CRC, as well as drug mechanisms, and focuses on the research progress of senescent tumors and stromal cells in CRC. Eventually, we discuss the strategies for CRC senescent cells after anti-cancer treatment to provide some theoretical basis and direction for retarding the malignant progression and recurrence of CRC.